Evaluation of the serum zinc level in patients with vitiligo - Mogaddam, Majid Rostami; Ardabili, Nastaran Safavi; Maleki, Nasrollah; Chinifroush, Mir Mehdi; Fard, Elham Maleki (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2017)
Introduction : Vitiligo is an acquired, idiopathic disorder characterized by circumscribed depigmented macules and patches, which affects approximately 0.1–2% of the general population worldwide. Zinc is an essential trace element that is necessary for growth and development at all stages of life. Some studies have reported an association between serum zinc levels and vitiligo. Aim : To measure the serum zinc level in patients with vitiligo compared to healthy subjects. Material and methods : One hundred patients with vitiligo and 100 healthy controls were referred to our clinic. The two groups were matched for age and sex. Atomic absorption spectrophotometry was used to measure serum zinc levels. The statistical analysis was performed using SPSS software. Results : The mean serum level of zinc in vitiligo patients and controls was 80.11 ±17.10 µg/dl and 96.10 ±16.16 µg/dl, respectively. The serum zinc level in patients with vitiligo was significantly lower than in healthy controls (p = 0.0001). Conclusions : The results of our study revealed a significant association between vitiligo and serum zinc levels. A relative decrease in the serum zinc level in vitiligo patients can highlight the role of zinc in the pathogenesis of vitiligo, and large-scale studies need to be conducted to confirm these findings and assess the effect of oral zinc supplements in patients with low zinc levels.